Hubungan Pengetahuan dan Faktor Lingkungan dengan Praktik Personal Hygiene saat Menstruasi pada Remaja Putri di Tingkat Sekolah Menengah Pertama (SMP) - Desi Rahmalia; Asyifa Robiatul Adawiyah; Dini Indah Lestari; Izattul Azijah (LPPM Universitas Respati Indonesia, 2026)
Personal hygiene practices during menstruation are an important aspect of maintaining the reproductive health of adolescent girls. Poor hygiene during menstruation can increase the risk of reproductive tract infections. However, many adolescent girls still pay little attention to menstrual hygiene, such as changing sanitary pads less than twice a day, not washing their hands before and after changing pads, not changing underwear regularly, and disposing of used pads carelessly. This study aimed to examine the relationship between knowledge and environmental factors with personal hygiene practices during menstruation among junior high school girls. A cross-sectional design was used with a total of 53 eighth-grade students at SMP Negeri 19 Bekasi, selected through purposive sampling. The research instrument was a questionnaire and data were analyzed using the Chi-Square test. The results showed a significant relationship between knowledge and personal hygiene practices during menstruation (p = 0.03; p < 0.05). In addition, there was a significant relationship between the home environment and personal hygiene practices (p = 0.046; p < 0.05). However, no significant relationship was found between the school environment and personal hygiene practices (p = 0.72; p > 0.05). It can be concluded that knowledge and the home environment very important role in menstrual personal hygiene practices